Socioeconomic Status Mediates Racial Differences Seen Using the AT(N) Framework. Issue 2 (7th November 2020) - Meeker, Karin L.; Wisch, Julie K.; Hudson, Darrell; Coble, Dean; Xiong, Chengjie; Babulal, Ganesh M.; Gordon, Brian A.; Schindler, Suzanne E.; Cruchaga, Carlos; Flores, Shaney; Dincer, Aylin; Benzinger, Tammie L.; et al.
Abstract : Objectives: African Americans are at greater risk for developing Alzheimer's disease (AD) dementia than non‐Hispanic whites. In addition to biological considerations (eg, genetic influences and comorbid disorders), social and environmental factors may increase the risk of AD dementia. This paper (1) assesses neuroimaging biomarkers of amyloid (A), tau (T), and neurodegeneration (N) for potential racial differences and (2) considers mediating effects of socioeconomic status (SES) and measures of small vessel and cardiovascular disease on observed race differences. Methods: Imaging measures of AT(N) (amyloid and tau positron emission tomography [PET]) structural magnetic resonance imaging (MRI), and resting state functional connectivity (rs‐fc) were collected from African American (n = 131) and white (n = 685) cognitively normal participants age 45 years and older. Measures of small vessel and cardiovascular disease (white matter hyperintensities [WMHs] on MRI, blood pressure, and body mass index [BMI]) and area‐based SES were included in mediation analyses. Results: Compared to white participants, African American participants had greater neurodegeneration, as measured by decreased cortical volumes (Cohen's f 2 = 0.05, p < 0.001). SES mediated the relationship between race and cortical volumes. There were no significant race effects for amyloid, tau, or rs‐fc signature. Interpretation: Modifiable factors, such as differences in social contexts and resources, particularly area‐level SES, may contribute to observed racial differences in AD. Future studies should emphasize collection of relevant psychosocial factors in addition to the development of intentional diversity and inclusion efforts to improve the racial/ethnic and socioeconomic representativeness of AD studies. ANN NEUROL 2021;89:254–265